2017
DOI: 10.1016/j.tourman.2017.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Founts of knowledge or delusions of grandeur? Limits and illusions of tourism research impact: A reply to Wood

Abstract: The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team.We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we will investigate on a case-by-case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…To prevent myths like these from continuing to color the debate on overtourism, it is recommended that academic researchers continue to engage with the issue, both through direct interaction with stakeholders [59], but also by building a strong body of academic output that informs teaching [60][61][62]. The literature review has already shown that there is a rich history of work to form the basis for future work.…”
mentioning
confidence: 99%
“…To prevent myths like these from continuing to color the debate on overtourism, it is recommended that academic researchers continue to engage with the issue, both through direct interaction with stakeholders [59], but also by building a strong body of academic output that informs teaching [60][61][62]. The literature review has already shown that there is a rich history of work to form the basis for future work.…”
mentioning
confidence: 99%